2014
DOI: 10.1371/journal.pone.0111379
|View full text |Cite
|
Sign up to set email alerts
|

The SbMT-2 Gene from a Halophyte Confers Abiotic Stress Tolerance and Modulates ROS Scavenging in Transgenic Tobacco

Abstract: Heavy metals are common pollutants of the coastal saline area and Salicornia brachiata an extreme halophyte is frequently exposed to various abiotic stresses including heavy metals. The SbMT-2 gene was cloned and transformed to tobacco for the functional validation. Transgenic tobacco lines (L2, L4, L6 and L13) showed significantly enhanced salt (NaCl), osmotic (PEG) and metals (Zn++, Cu++ and Cd++) tolerance compared to WT plants. Transgenic lines did not show any morphological variation and had enhanced grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…Reactive oxygen species (ROS) are generated in response to stress, causing oxidative damage to the cell; therefore, plants exhibit robust defence mechanisms against ROS-induced oxidative stress [7,25,44,60].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are generated in response to stress, causing oxidative damage to the cell; therefore, plants exhibit robust defence mechanisms against ROS-induced oxidative stress [7,25,44,60].…”
Section: Introductionmentioning
confidence: 99%
“…Some species of Salicornia have shown important biological properties, such as antioxidant, anti-inflammatory, hypoglycemic and cytotoxic activities (Isca, Seca, Pinto, & Silva, 2014). Furthermore, Salicornia is being widely explored for abiotic stress-responsive genes and promoters to develop transgenic plants that can withstand adverse environmental conditions (Chaturvedi, Mishra, Tiwari, & Jha, 2012;Chaturvedi, Patel, Mishra, Tiwari, & Jha, 2014;Jha, Sharma, & Mishra, 2011;Singh, Mishra, & Jha, 2014a, 2014bUdawat, Mishra, & Jha, 2014). No information is available, so far, on the metabolomics of this important succulent halophytic plant.…”
Section: Introductionmentioning
confidence: 99%
“…Graph represents the mean ± SE (n = 3) followed by similar lower case letter are significantly not different according to Tukey's multiple range at P B 0.05 (this is the same for Figs. 3, MDA concentration in T lines at higher salt treatment (3 dS m -1 ), compared to WT, suggested that T plants had balanced ROS formation and suffered less oxidative lipid injury than WT lines(Tang et al 2005;Rai et al 2013).Similarly, lower in situ accumulation of O 2 -and H 2 O 2 was reported in SbMT-2 tobacco(Chaturvedi et al 2014), AhAREB1 Arabidopsis(Li et al 2013), and lower MDA content in mtlD tomato(Khare et al 2010) and MuNAC4…”
mentioning
confidence: 87%
“…This includes lowmolecular-mass non-enzyme antioxidant metabolites, such as ascorbic acid and various antioxidant enzymes such as SOD, CAT, APX, GR and POD (Bhatnagar-Mathur et al 2009;Miller et al 2010;Chaturvedi et al 2014). Ascorbic acid (AsA) is both a secondary metabolite and an antioxidant which interacts enzymatically and non-enzymatically and detoxifies the ROS (Upadhyaya et al 2011).…”
Section: Relative Water Content (Rwc)mentioning
confidence: 99%